The Outcomes of Transcatheter Closure in Patients with Patent Ductus Arteriosus at Haji Adam Malik General Hospital, Indonesia - Amelia, Putri; Adriansyah, Rizky; Lubis, Bastian; Akil, Muhammad (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Patent ductus arteriosus (PDA) is one of the most common acyanotic congenital heart diseases. The incidence of PDA is approximately 1 in 500 full-term neonates. The current management of PDA includes pharmacological and surgical treatments. Transcatheter closure is a preferable PDA treatment than pharmacological intervention, for medications have a higher failure rate in premature infants. Several studies have reported the efficacy and safety of transcatheter closure in smaller and lower-weight infants. AIM: This study aims to describe the outcomes of transcatheter closure of PDA, which are complete closure, migrating device, and residuals, while also investigating factors that might affect these outcomes. METHODS: A descriptive cross-sectional study was conducted from January to March 2018 in the pediatric cardiology outpatient clinic of Haji Adam Malik Hospital, Medan, Indonesia. All PDA patients who underwent transcatheter closure were included in this study. We collected patients’ demographic data (age and sex), PDA size (categorize into large, moderate, and small), and PDA closure outcomes from medical records. The collected data were then analyzed with SPSS. RESULTS: One hundred and two children were included in this study, comprised 34 (33.3%) males and 68 (66.7%) females, with a mean age of 4.3 (±4.02) years old and the mean size of the defects 4.4 (±2.25) mm. Transcatheter closure with Lifetech® PDA Occluder was performed in 95 (93.1%) and MFO® in 7 (6.9%) patients. Small residuals were found in three patients, device migration was found in one patient. No relationship was found between the size of PDA and the outcomes measured. CONCLUSION: We concluded that transcatheter closure remains an effective treatment for PDA, with a considerable success rate.